(untitled) (Indo-MathEdu Intellectuals Journal, 2024)
The ability that can support success in the learning process and can solve various mathematical problems is the ability to solve mathematical problems. This research is related to quantitative research which examines students’ mathematical problem solving abilities using the HLT model and mathematical disposition as covariate variables. This research aims to determine the effect of the HLT model on mathematical problem solving abilities by controlling students’ mathematical dispositions, and the influence of mathematical dispositions on students’ mathematical problem solving abilities, as well as the simultaneous influence of the HLT model and mathematical disposition on students’ mathematical problem solving abilities. 70 junior high school students using cluster random sampling, where 35 students studied using the HLT model and 35 students studied using the direct instruction model. The tools used to collect data are a mathematical disposition questionnaire and a description test of mathematical problem solving abilities. This data analysis uses analysis of covariance (one-way ANCOVA). The results of the hypothesis test show that there is an influence of the mathematical disposition covariate variable by controlling students’ mathematical disposition and there is an influence of the mathematical disposition covariate variable on students’ mathematical problem solving abilities, and there is a simultaneous influence of the HLT model and mathematical disposition on students’ mathematical problem solving abilities